A desriptive analysis of anglicism used in Ecuadorian magazines - Erique Guajala, Favio Steve (2012)
This research is a descriptive analysis of the anglicisms in Ecuadorian magazines phenomenon. It was conducted in Guayaquil, Ecuador, and there were three variables used for the study: general interest magazines, cultural magazines and scholarly magazines. Samples from these variables were analyzed, resulting in three lists of anglicisms, one per variable. A linguistic analysis was conducted on thirty of the words that were the most representative or presented themselves as the most interesting cases, in order to explain and describe any morphological, syntactical or semantical changes from their original English forms. Results show a significant presence of anglicisms in scholarly magazines, followed by general interest magazines, and finally cultural magazines. Scholarly magazines’ subjects were Economics and Technology. According to this analysis, anglicisms presence in Ecuadorian magazines is justified by the lack of Spanish equivalents rather than prestige or other socio-cultural reasons.